Persepsi dan Tantangan Sertifikasi Perikanan Berkelanjutan oleh Perusahaan Pengolahan Produk Perikanan - Arsyad, Padma Rizki Dwi Arieanti; Rahayu, Winiati P.; Nurjanah, Siti (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2025)
The Sustainable Development Goals (SDGs) reflect a commitment to utilizing natural resources for human well-being. This includes efforts to promote a sustainable food system, including fishery products known as blue food. Sustainable aquaculture certification is important to ensure that products come from responsible sources, considering aspects of food safety, environment, animal welfare, and social responsibility. This study aims to assess the perception of companies towards the certification, including knowledge, attitudes, behaviors, and challenges in sustainable aquaculture certification. The survey was conducted on thirty respondents from aquaculture processing companies, divided into fifteen certified companies and fifteen uncertified companies. Certified companies showed good knowledge and attitude percentage scores (100%), and good behavior (93.3%). Meanwhile, uncertified companies had good knowledge (80%) and attitude (93.3%), but lower behavior (73.3%). This shows a behavioral gap in the uncertified group, even though they have a positive attitude towards sustainability certification. Significant correlations (p<0.05) between variables were identified between knowledge-behavior (rs=0.515), attitude-behavior (rs=0.639), attitude-challenge (rs=0.620), and behavior-challenge (rs=0.902). In uncertified companies, no significant correlation was found. This finding indicates that certified companies have a strong relationship between understanding, attitude, and behavior even though the companies are aware of the major challenges in implementation, while uncertified companies face structural or motivational barriers that hinder behavior even though they have a positive attitude. The main challenge faced by certified and uncertified companies is the limited knowledge of the team in implementation, with percentages of 40 and 46%, respectively. In addition, both groups of companies also face challenges related to the excessive cost of certification, which is recognized by 33% of each group.